Comparison of Antibody Responses to Human Papillomavirus Vaccination as Measured by Three Assays - Robbins, Hilary A.; Kemp, Troy J.; Porras, Carolina; Rodriguez, Ana Cecilia; Schiffman, Mark; Wacholder, Sholom; Gonzalez, Paula; Schiller, John; Lowy, Douglas; Poncelet, Sylviane; Esser, Mark; Matys, Katie; et al. (Frontiers in Oncology, 2014)
Background: Different assays, including the competitive Luminex immunoassay (cLIA), secreted alkaline phosphatase neutralization assay (SEAP-NA), and virus-like particle-based ELISA, are commonly used to measure antibody responses after human papillomavirus (HPV) vaccination. Direct assay comparisons aid interpretation of immunogenicity data evaluated by different assays. Methods: We compared cLIA to SEAP-NA and ELISA among 51 HPV16/18-vaccinated women enrolled in the Costa Rica Vaccine Trial. We tested replicate serum samples collected at months 0, 1, and 12 by HPV16/18 cLIA, SEAP-NA, and ELISA. For a subset (N = 10), we further tested month 6, 24 and 36 samples. We calculated seroprevalence estimates and Spearman rank correlation coefficients comparing cLIA to SEAP-NA and ELISA. Results: After one vaccine dose, seroprevalence by SEAP-NA and ELISA was 100% (both HPV16 and HPV18), and by cLIA was 96% (95% CI 87–100%) for HPV16 and 71% (95% CI 56–83%) for HPV18. Seroprevalence was 100% by all assays after three doses. Correlation between assays was high after one vaccine dose [cLIA/SEAP-NA ρ = 0.91 (HPV16) and ρ = 0.86 (HPV18); cLIA/ELISA ρ = 0.84 (HPV16) and ρ = 0.74 (HPV18); all p < 0.001] and remained high through month 36. Ratios of mean antibody levels to seropositivity cutoffs at month 36 were lower for cLIA than for SEAP-NA or ELISA, particularly for HPV18 (HPV18 ratio for cLIA 1.9, SEAP-NA 3.5, ELISA 3.4). Conclusion: Though correlation between cLIA and SEAP-NA/ELISA is high and stable after vaccination, the assays differ in scale and sensitivity, with notable differences after one vaccine dose and for HPV18. Our results demonstrate that comparisons of antibody responses to HPV vaccination measured by different assays are approximate, and must consider biological and technical differences between assays.